Ghosts in the machine: understanding digital citizenship as the struggle of students' souls with classroom technology. Issue 2 (2nd April 2020) - Lucey, Thomas A.; Lin, Miranda
ABSTRACT: Through this paper, the authors describe the challenge of interpreting and teaching digital citizenship in the classroom. They present digital citizenship as a concept that features a range of applications influenced by teacher and student traits. They begin with an explaination of the advent of digital/screen technology, and describe it as a corporately sanctioned addictive presence. They review the concepts of, Spirituality and digital citizenship, before introducing critical compassion as an additional dimension for understanding digital citizenship and the conditions that influence it. The authors describe a model that depicts critical compassion's relationship to digital citizenship and offers as a basis for strategies that concern teacher training, instructional practice, and professional direction.